Programmatic factors associated with the limited impact of Community-Directed Treatment with Ivermectin to control Onchocerciasis in three drainage basins of South West Cameroon. - Christian Tetteh Duamor; Fabrice Roberto Datchoua-Poutcheu; Winston Patrick Chounna Ndongmo; Aldof Tah Yoah; Ernest Njukang; Emmanuel Kah; Mary Sheena Maingeh; Jonas Arnaud Kengne-Ouaffo; Dizzle Bita Tayong; Peter A Enyong; Samuel Wanji (Public Library of Science (PLoS), 2017)
The CDTI model is known to have enhanced community participation in planning and resource mobilization toward the control of onchocerciasis. These effects were expected to translate into better individual acceptance of the intervention and hence high Treatment Coverage, leading to a sustainable community-led strategy and reduction in the disease burden. A survey revealed that after 10-12 rounds of treatment, prevalence of onchocerciasis was still high in three drainage basins of South West Cameroon and transmission was going on.We designed a three (3)-year retrospective (2012, 2013 and 2014), descriptive cross-sectional study to explore the roles of operational challenges in the failure of CDTI to control the disease as expected. We administered 83 semi-structured questionnaires and conducted 12 in-depth interviews with Chiefs of Bureau Health, Chiefs of Centers, CDDs and Community Heads. Descriptive statistics was used to explore indicators of performance which were supported with views from in-depth interviews.We found that community participation was weak; communities were not deciding time and mode of distributions. Only 6 (15.0%) of 40 Community Drug Distributors reported they were selected at general community meetings as required. The health service was not able to meet and discuss Community-Directed Treatment with Ivermectin activities with individual communities partly due to transportation challenges; this was mostly done through letters. Funding was reported to be inadequate and not timely. Funds were not available to conduct Community-Self Monitoring after the 2014 Mass Drug Administration. There was inadequate health staff at the frontline health facility levels, and some Chiefs of Center reported that Community-Directed Treatment with Ivermectin work was too much for them. The mean operational Community Drug Distributor-population ratio was 1 Community Drug Distributor per 317 populations (range: 194-464, expected is 1:250). Community Drug Distributor attrition rate was 14% (2012), 11% (2013) and 12% (2014) of total Community Drug Distributors trained in the region. Lack of incentive for Community Drug Distributor was primary reason for Community Drug Distributor attrition. Number of Community Drug Distributors trained together by health area ranged from 14 to 127 (mean ± SD = 51 ±32) with duration of training ranging from 4-7 hours (mean ± SD = 5.05 ± 1.09). The trainings were conducted at the health centers. Community Drug Distributors always conducted census during the past three distributions (Mean ± SD = 2.85 ± 0.58). Community-Self Monitoring was facing challenge. Several of the community heads, Chiefs of Bureau Health and Chiefs of Center agreed that Community-Self Monitoring was not being carried out effectively due to lack of incentives for monitors in the communities.Inadequate human resource, funding issues and transportation challenges during distribution periods reduced the ability of the health service to thoroughly sensitize communities and supervise CDTI activities. This resulted in weak community understanding, acceptance and participation in the process. CDTI in our study area did not achieve sustainable community-led campaign and this may have led to the reduced impact on Onchocerciasis.